The reflection of BC over I is shown below.
<h3>
What is reflection?</h3>
- A reflection is a mapping from a Euclidean space to itself that is an isometry with a hyperplane as a set of fixed points; this set is known as the reflection's axis (in dimension 2) or plane (in dimension 3).
- A figure's mirror image in the axis or plane of reflection is its image by reflection.
See the attached figure for a better explanation:
1. By the unique line postulate, you can draw only one line segment: BC
- Since only one line can be drawn between two distinct points.
2. Using the definition of reflection, reflect BC over l.
- To find the line segment which reflects BC over l, we will use the definition of reflection.
3. By the definition of reflection, C is the image of itself and A is the image of B.
- Definition of reflection says the figure about a line is transformed to form the mirror image.
- Now, the CD is the perpendicular bisector of AB so A and B are equidistant from D forming a mirror image of each other.
4. Since reflections preserve length, AC = BC
- In Reflection the figure is transformed to form a mirror image.
- Hence the length will be preserved in case of reflection.
Therefore, the reflection of BC over I is shown.
Know more about reflection here:
brainly.com/question/1908648
#SPJ4
The question you are looking for is here:
C is a point on the perpendicular bisector, l, of AB. Prove: AC = BC Use the drop-down menus to complete the proof. By the unique line postulate, you can draw only one segment, Using the definition of, reflect BC over l. By the definition of reflection, C is the image of itself and is the image of B. Since reflections preserve , AC = BC.
Answer:
D.68ft
Step-by-step explanation:
f(x) = 7x² - 3x + 1
g(x) = 3x - 2
1. g(0) This means that x is 0, so you can plug in 0 for x in the equation:
g(x) = 3x - 2
g(0) = 3(0) - 2
g(0) = -2
2. g(1) x is 1
g(x) = 3x - 2
g(1) = 3(1) - 2
g(1) = 3 - 2
g(1) = 1
3. f(1) x is 1
f(x) = 7x²- 3x + 1
f(1) = 7(1)² - 3(1) + 1
f(1) = 7 - 3 + 1
f(1) = 5
4. f(x) = 7x²- 3x + 1
f(-2) = 7(-2)²- 3(-2) + 1
f(-2) = 7(4) + 6 + 1
f(-2) = 28 + 7
f(-2) = 35
4 units wide
Any more help feel free to ask